Surgical management of skeletal metastases of the appendicular skeleton. Issue 3 (June 2017) - Taylor, John; Kumar, Amit
Abstract: Skeletal metastases are a common cause of morbidity in cancer patients through bone pain, pathological fracture and spinal cord compression. With advances in surgical and medical treatment, and a multidisciplinary approach, the outcome and survival for these patients has improved in recent years. The orthopaedic surgeon should be an integral part of the multidisciplinary team who provide high quality treatment to these patients to optimize outcome. They should be aware of the particular needs of these patients and the range of surgical and non-surgical treatments available. This article outlines the presentation, diagnosis and surgical management of patients with skeletal metastases. It summarizes the relevant best practice guidelines applicable to surgeons working in the UK but with worldwide relevance.